THE GLOBAL ROLE OF PHILOSOPHY IN EDUCATION TRENDS: TRADITIONAL AND COMPARISON OF MODERN APPROACHES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the historical changes in philosophical approaches to education and a new educational paradigm formed on the basis of contemporary global trends. Whereas the traditional model of education is more discipline-based, modern education is characterized by a humanitarian, competency approach, digital literacy and the development of critical thinking. The study compares the ontologic, axiological, and epistemological foundations of traditional and new educational philosophies.